Efforts to Improve Student Learning Outcomes at SD Negeri Napai through Sharing and Audio Visual Media on the Material When Life Has Stopped - Yusmalita; A, Saudah (Jurnal Profesi Guru Indonesia, 2025)
This study aims to improve the learning outcomes of grade V students of SD Negeri Napai in the subject of Islamic Religious Education and Ethics through the use of audio-visual media with the shering method. Based on the results of initial observations, only about 25% of students achieved the Minimum Completeness Criteria (KKM) with an average score of 68, below the KKM set of 70. The learning conditions are not conducive and the students' interest in learning is relatively low. This research was carried out with two cycles of learning actions that used audio-visual media as an interactive learning medium with the material "When Life Has Stopped." After the application of this method, there was a significant increase in student learning outcomes, where the percentage of students who achieved KKM increased to 83%, and the average class score increased to 78. In addition, students' interest and motivation for learning also show positive development. These findings indicate that the use of audio-visual media with the shering method is effective in improving students' understanding of concepts and learning outcomes. Therefore, audio-visual media can be used as a more interesting learning alternative and help teachers in improving the quality of learning in Islamic Religious Education and Ethics.